Sistem Pengambilan Keputusan Untuk Rekomendasi Pembelian Produk Dengan Menggunakan Metode Fuzzy MCDM - Jarot, Jarot Dian Susatyono; Febryantahanuji Febryantahanuji; Iddo Elianta Herlambang (STEKOM PRESS, 2020)
PT. Nerangi Sarana Karya often experiences several problems because of the large number of purchases purchased but there is no system that helps to recommend product purchases, for example on 9 October 2018 PT. To solve the problems that occur at PT Nerangi Sarana Karya, it is necessary to apply a decision making system using the Fuzzy MCDM method, based on the results of data testing that this method has an accuracy rate of data analysis of 87% so that this method is quite feasible to use in decision making.